Transient Numerical Simulation of Combustion in Inert Porous Media - Knabner, Peter; De Neef, Michel J.; Summ, Gerhard (ZAMM - Zeitschrift für angewandte Mathematik und Mechanik, 1999)
This paper presents methods for the time-dependent numerical solution of a two-dimensional model governing combustion an inert porous media. The spatial discretization is based on a mixed finite element method for the flow problem and a cell-centered finite volume scheme for the transport equations. Some results of numerical simulations show the influence of a jump in the porosity of the solid matrix on the localization of the combustion zon